Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper describes recent investment dynamics in Peru, and assesses the relationship between private investment and its fundamentals. Over the last decade, average growth in Peru exceeded 6 percent, anchored by a substantial contribution from investment. A series of structural reforms in the 1990s, growing political stability, and the implementation of a solid macroeconomic framework in the early 2000s set the stage for this investment boom. Actions were also taken to strengthen public investment implementation and to enhance the overall investment climate. Now that commodity prices have softened and interest rates are expected to rise, addressing the next generation of structural reforms will be crucial to sustain investment and growth.